FEATURES OF REPRODUCTIVE MOTIVATION AND EMOTIONAL STATE OF PREGNANT WOMEN - Оксана Владимировна Носкова; Андрей Викторович Чурилов; Галина Васильевна Былым; Елена Валерьевна Литвинова (The Publishing House Medicine and Enlightenment, 2024)
The purpose of the work - studying the characteristics of reproductive motivation and emotional state of pregnant women. Materials and methods. 42 pregnant women aged 18 to 42 years were examined in the pregnancy pathology department of the Donetsk Clinical Territorial Medical Association. The following methods were used in the study: the Rokeach Terminal Values Scale, the «Attitude Test of Pregnant Women» technique; «Personal Anxiety Scale» (J. Taylor); questionnaire «Current state», method by I.V.»Dobryakova «Attitude Test of Pregnant Women» to determine the type of psychological component of a woman's gestational dominance during pregnancy. Results. The highest value of the unborn child was recorded among women 26-30 years old (91.8 %) with a high level of education (85.7 %) from two-parent families. When analyzing the psycho-emotional state of pregnant women for the first time and those in the third trimester of pregnancy, it was revealed that the process of bearing a child is accompanied by increased anxiety for the unborn child and the upcoming birth with a predominance of the anxious type of gestational dominant was identified in 6 respondents (40 %), the optimal type in 2 (13,3 %), the predominance of the euphoric type in 4 (26.6 %) women, the hypogestognosic type was diagnosed in 2 (13.3 %) women. The severity of the depressive type was identified in 1 (6.7 %). Conclusion. When analyzing the psycho-emotional state of pregnant women for the first time and those in the third trimester of pregnancy, it was revealed that the process of bearing a child is accompanied by increased anxiety for the unborn child and the upcoming birth with a predominance of the anxious type of gestational dominant. The data obtained indicate that the psycho-emotional state of pregnant women who have not previously given birth requires more careful consideration and psycho-corrective measures